Dampak Islamic Intellectual Capital dan Islamic Social Reporting terhadap Maqashid Syariah Performance: Peran Moderasi Islamic Corporate Governance - Firman Jofani; Endri Endri; Saiful Anwar (ITB AAS INDONESIA Surakarta, 2023)
This study aims to determine the impact of Islamic Intellectual Capital and Islamic Social Reporting on Maqashid Syariah Performance with the Moderation role of Islamic Corporate Governance. The method used in this research is associative quantitative method. While the data used in this study is secondary data. The population in this study is the largest bank in the world version of The Asian Banker 2020 in the period of 2016 - 2021. The sample used in this study is the 10 largest banks in the world version of The Asian Banker with an observation period of 6 years in the 2016 - 2021 period, so there are 60 observational data. Data analysis used descriptive statistical analysis and Moderated Regression Analysis (MRA). The analytical tool used in this research is analysis with the help of the Eviews version 9. The results of this study indicate that simultaneously the Islamic Intellectual Capital (iB-IC) and Islamic Social Reporting (ISR) variables have an effect on Maqashid Syariah Performance (MSP). Partially the Islamic Intellectual Capital variable has a significant positive effect on Maqashid Syariah and the Islamic Social Reporting variable has no effect on Maqashid Syariah Performance. The moderation test shows that the Islamic Intellectual Capital Variable cannot moderate the effect of Islamic Intellectual Capital on Maqasyid Syariah Performance and the Islamic Corporate Governance Variable can moderate the effect of Islamic Social Reporting on Maqasyid Syariah Performance.